If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9d = 9 + 10d Solving 9d = 9 + 10d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-10d' to each side of the equation. 9d + -10d = 9 + 10d + -10d Combine like terms: 9d + -10d = -1d -1d = 9 + 10d + -10d Combine like terms: 10d + -10d = 0 -1d = 9 + 0 -1d = 9 Divide each side by '-1'. d = -9 Simplifying d = -9
| 4x^2-35x-414= | | 3w+15=48 | | 10B+8=68 | | -5(r+4)=-72 | | 10-7r=8-9r | | 2.4k=18.96 | | 4x^2+35x-414= | | 10y-12=48 | | 5(x+6)-7x=26 | | 3w+13=34 | | 7m-10=9m+4 | | 20x-7=3+18 | | .72x+2.4x+32.58=.89x-.55x | | -2t+7=5t | | -3f=-f-10 | | x-8=-2x+3 | | -10u=-9-9u | | -4(x-3)-3x=2(6-3x)-3x | | -6+14+4=32 | | W+(w+2)=-27 | | 10+6z=5z | | 9p-10=10p | | 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 |